The Influence of Compensation, Competence, Work Environment, and Job Placement on Employee Per-formance at PT XYZ Cigarette Industry in Pasuruan with Motivation as an Intervening Variable - Nugroho, Catur Bayu; Sukoco, Agus (LPPM of NAROTAMA UNIVERSITY, 2025)
This study aims to examine how compensation, competence, job placement, and work environment influence employee performance, with motivation acting as an intervening variable. The research is conducted within the context of the cigarette industry in Pasuruan, Indonesia. Given the industry's challenges, such as rising excise taxes and regulatory pressures, it is crucial to understand these organizational factors to enhance workforce effectiveness. A quantitative approach was employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). The study involved 52 technical employees electronic division at PT XYZ, selected through saturated sampling. Data were collected using structured questionnaires and analyzed with SmartPLS 3.0. The findings show that compensation has a significant effect on employee performance. In contrast, competence, work environment, and job placement have no significant direct effect on employee performance. Compensation, competence, and job placement do not significantly affect motivation, while work environment has a significant positive effect on motivation. Furthermore, motivation significantly improves employee performance. Regarding the mediating role of motivation, the results indicate that motivation does not mediate the relationship between compensation and performance, competence and performance, nor job placement and performance. However, motivation is proven to mediate the effect of work environment on performance. These findings emphasize the strategic importance of creating a supportive work environment and enhancing motivation to improve employee performance.